The Egyptian Red Sea coastal microbiome: A study revealing differential microbial responses to diverse anthropogenic pollutants. (July 2016) - Mustafa, Ghada A.; Abd-Elgawad, Amr; Ouf, Amged; Siam, Rania
Abstract: The Red Sea is considered one of the youngest oceanic systems, with unique physical, geochemical and biological characteristics. Tourism, industrialization, extensive fishing, oil processing and shipping are extensive sources of pollution in the Red Sea. We analyzed the geochemical characteristics and microbial community of sediments along the Egyptian coast of the Red Sea. Our sites mainly included 1) four ports used for shipping aluminum, ilmenite and phosphate; 2) a site previously reported to have suffered extensive oil spills; and 3) a site impacted by tourism. Two major datasets for the sediment of ten Red Sea coastal sites were generated; i) a chemical dataset included measurements of carbon, hydrogen, nitrogen and sulfur, metals and selected semi-volatile oil; and ii) a 16S rRNA Pyrotags bacterial metagenomic dataset. Based on the taxonomic assignments of the 16S rRNA Pyrotags to major bacterial groups, we report 30 taxa constituting an Egyptian Red Sea Coastal Microbiome. Bacteria that degrade hydrocarbons were predominant in the majority of the sites, particularly in two ports where they reached up to 76% of the total identified genera. In contrast, sulfate-reducing and sulfate-oxidizing bacteria dominated two lakes at the expense of other hydrocarbon metabolizers. Despite the reported "Egyptian Red Sea Coastal Microbiome, " sites with similar anthropogenic pollutants showed unique microbial community abundances. This suggests that the abundance of a specific bacterial community is an evolutionary mechanism induced in response to selected anthropogenic pollutants. Graphical abstract: Highlights: 30 different bacterial taxa constitute the "Egyptian Red Sea Coastal Microbiome. Hydrocarbon degradering bacteria constitute 76% of the total identified genera in two Red Sea coastal sites. Abundance of sulfur oxidizers and reducers and reduced abundance of hydrocarbon degraders in two Red Sea lakes. Distinct chemical clustering/profile in Red Sea ports, with a sub-clustering in phosphate versus ilmenite and aluminum port. Microbial communities in marine coastal sites seem to be affected by intrinsic characteristics and extrinsic anthropogenic factors. Abstract : An environmental genomic approach describes the dominance of hydrocarbon degraders or sulfur metabolizers in the Red Sea Coastal Microbiome in response to anthropogenic pollutants.